Analisis Kesantunan Berbahasa dalam Pertanyaan Interogasi BAP: Kajian Linguistik Forensik dan DampakPsikologis pada Saksi - Saud, Jefriyanto; Lustyantie, Ninuk; Murtadho, Fathiaty (Jurnal Ilmiah Global Education, 2025)
The language in the Police Investigation Report (BAP) is very important, yet interrogations in Indonesia often neglect politeness, resulting in suggestive and intimidating questions that can pressure witnesses, damage their "face," and disrupt memory accuracy. This research fills the gap in studies in Indonesia that have not yet holistically integrated pragmatic politeness theory (Brown & Levinson, Leech) with psycholinguistic and cognitive impacts (Sweller's cognitive load, Gernsbacher & Levelt's disfluency) on BAP witnesses. The aim is to identify the forms and violations of politeness in BAP questions, evaluate their psychological impact on witnesses, and formulate recommendations for fairer interrogations. This descriptive qualitative research analyzes BAP data using the politeness theory of Brown & Levinson and Leech (modified with "mitigation tools" for forensic contexts), as well as Sweller's cognitive load theory and Gernsbacher & Levelt's psycholinguistics to analyze witness responses (focusing on disfluency and lexical access). A layered analysis scheme is used to link politeness violations with the intensity of cognitive load. Validity is ensured through theory triangulation, peer debriefing, member checking, and audit trail. It is expected that this research will produce a multidimensional evaluation model and practical recommendations for fairer and more effective interrogation practices